2016
DOI: 10.7729/82.1193
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Peer Membership of School Counselors and the Resources Used Within Their Decision-Making

Abstract: The purpose of this study was to describe the demographic identity of a national sample of professional school counselors who were members of the American School Counselor Association (ASCA), understand the manner in which they conceptualized their professional peer membership, and explore what sources they use to make professional and ethical decisions. Consistent with previous research, the majority of participants were white woman, across all four regions in the sample; however, when compared to previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Internalizing the profession's values and understanding it occurs mainly during fieldwork in the schools. Practical training was found critical for constructing the counselor's professional identity and understanding of the profession (Gilbride et al, 2016;Moyer & Yu, 2012). Studies that explored the professional identity of school counselors during their training found that proper and meaningful fieldwork during academic studies induced significant impact on counselor's further work and their professional identity (Brott & Myers, 1999;Gilbridge et al, 2016;Moss et al, 2014;Moyer & Yu, 2012;).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internalizing the profession's values and understanding it occurs mainly during fieldwork in the schools. Practical training was found critical for constructing the counselor's professional identity and understanding of the profession (Gilbride et al, 2016;Moyer & Yu, 2012). Studies that explored the professional identity of school counselors during their training found that proper and meaningful fieldwork during academic studies induced significant impact on counselor's further work and their professional identity (Brott & Myers, 1999;Gilbridge et al, 2016;Moss et al, 2014;Moyer & Yu, 2012;).…”
Section: Discussionmentioning
confidence: 99%
“…Internalizing the profession's values and understanding, occur mainly during the practical experience. Indeed, studies have found that practical training is critical for building the counselor's professional identity and understanding of the profession (Gilbride, Goodrich, & Luke, 2016;Moyer & Yu, 2012).…”
Section: The Counselor's Areas Of Occupationmentioning
confidence: 99%
“…All three levels of education (i.e., elementary, middle, and high school) and varied demographic areas of service (rural, urban, and suburban) were represented by the participants. The demographics of the participants can be found in Table 1 and closely mirror the demographic breakdown of the membership of the American School Counselor Association (Gilbride et al, 2016). The age of the participants ranged from 26 to 64 years ( M = 41.3).…”
Section: Methodsmentioning
confidence: 95%
“…Along with the professions' ethical codes and standards, school counselors have additional resources (e.g., federal, state, and local laws and statutes; school board policies, consulting peers) available for guidance when faced with complex ethical dilemmas (Moyer et al, 2012). Notwithstanding, Gilbride et al (2016) reported that school counselors' primary source was administrative policy. Consulting with a colleague or professor was identified as one of the top three resources (Gilbride et al, 2016).…”
Section: Resources To Support Ethical Decision Makingmentioning
confidence: 99%
“…Notwithstanding, Gilbride et al (2016) reported that school counselors' primary source was administrative policy. Consulting with a colleague or professor was identified as one of the top three resources (Gilbride et al, 2016).…”
Section: Resources To Support Ethical Decision Makingmentioning
confidence: 99%